The participation of deaf and hard of hearing children in non-formal science activities - García-Terceño, Eva M.; Greca, Ileana M.; Santa Olalla-Mariscal, Gemma; Diez-Ojeda, María (Frontiers in Education, 2023)
Non-formal education is an important resource to foster scientific competence for active and responsible citizenship. However, these spaces do not always have the necessary requirements for everyone to access and participate. Therefore, with the intention of contributing to the creation of barrier-free spaces, the present study aims to identify the most appropriate psycho-pedagogical supports for the design and implementation of a scientific activity for a group of deaf and hard of hearing children. To achieve this objective, an instrumental case study was employed. The results, obtained through direct observation, satisfaction questionnaires, and interviews, show great interest among the children and both the sign interpreters accompanying the sessions and the organizers from the association assessed the activity in a positive light. These results also point to the need for spaces that could initially be controlled and that might strengthen the expectations among the participants and their families of participation in similar initiatives within more heterogeneous groups.